THE INFLUENCE OF PROJECT-BASED LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN GENERAL JOURNAL SUBJECT FOR GRADE X AT SMK NEGERI 1 PEMATANGSIANTAR - Ikke Seventiana; Binsar Tison Gultom; Debbi Petra Meyana Sitorus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to examine the effect of Project-Based Learning (PBL) model on the learning outcomes of students in the General Journal subject for grade X Accounting and Financial Institution program at SMK Negeri 1 Pematangsiantar. The background of this research is based on the low learning outcomes of students, which have not met the Minimum Competency Criteria (KKM), caused by conventional teaching methods that are less varied and limited active involvement from students during the learning process.This research employs a quantitative method with a quasi-experimental design using a Pretest-Posttest Control Group Design approach. The sample consisted of two classes: an experimental class taught using the Project-Based Learning model, and a control class taught using conventional methods. The instrument used was a 35-item multiple-choice test that had been validated and tested for reliability. Data analysis was performed using the non-parametric Wilcoxon Signed Rank Test due to the non-normal distribution of data as determined by the Kolmogorov-Smirnov and Shapiro-Wilk normality tests. The results revealed a significant increase in learning outcomes for the experimental class compared to the control class. The average pretest and posttest scores of the experimental class increased from 43.71 to 74.29, while the control class scores increased from 38.00 to 66.43. Wilcoxon test results showed a significance value of p = 0.000 (<0.05) for both classes, indicating that the improvement in learning outcomes was statistically significant. This demonstrates that the implementation of the Project-Based Learning model effectively enhances students’ conceptual understanding and skills in the General Journal subject. The study concludes that Project-Based Learning has a significant positive effect on improving student learning outcomes. Therefore, it is recommended that teachers and schools consistently implement this model in teaching to create a more active, creative, and enjoyable learning environment, as well as to sustainably improve student achievement. Furthermore, this study can serve as a reference for future research development in vocational learning or other subjects relevant to workforce demands.